The Role of Diffusion Weighted Imaging in Magnetic Resonance to Evaluate Breast Masses - Ozbalcı, Aysu Basak; Öztürk, Emine; Yücesoy, Cüneyt; Özbalcı, Gökhan Selçuk; Seker, Gaye Ebru (My University, 2020)
Aim: To investigate the role of diffusion weighted magnetic resonance imaging (MRI) indifferentiation of benign and malignant breast lesions using apparent diffusion coefficient (ADC)values preoperatively.Methods: A total of 30 women between the ages of 14-75 years (mean, 47, 6 years) with 30histopathologically verified breast lesions were investigated in this study. The patients were examinedby a 1 , 5 T MRI device using bilateral phased array breast coil. Spin echo planar diffusion imagingwas used to scan patients. Images were obtained by b values 0 and 500 seconds/mm². Mean ADCvalues of the benign and malignant lesions were measured and calculated. The comparison betweenthe histopathological diagnoses and the mean ADCs were performed by Mann Whitney U test.Results: The diagnosis of 30 patients with 30 breast lesions were as follows; malign lesions (n=13),benign lesions (n=17). The ADC values were as follows (in units of 10-3mm² /sec): benign breastlesions (range: 1, 09-1, 98, mean: 1 , 45) and malignant breast lesions (range: 0, 59-1, 08, mean: 0,76). The mean ADC obtained from malignant breast lesions was statistically different from thatobserved in benign solid lesions (p<0, 01).Conclusion: Diffusion imaging can be used in differentiation of malign and benign breast lesions.
Keywords: Onkoloji; Radyoloji; Nükleer Tıp; Tıbbi Görüntüleme